Integração de ferramentas para um firewall modular e escalável com uso de containers e computadores de placa única - Almeida, Mateus Mantoan de (2021)
Firewall is the name given to security systems found in computer networks, and having an efficient firewall is essential for any institution, however there are few low-cost options on the market. Currently, the concepts of high availability, scalability and hardware aggregation options to suit the demand for processes and modularize systems are widely discussed in the Information Technology market. Based on these principles, it is interesting to carry out a study for the integration of services for the provision of a low-cost firewall based on open source tools, using concepts of software and hardware modularization and high availability. This work aims to present concepts and tools that allow the provision of a low-cost, modular firewall that is compatible with open source security tools, to serve small and medium-sized companies or institutions, being applicable in a real environment. The results presented demonstrate that, with a low investment, the system can perform the analysis and treatment of traffic, as well as execute the chosen applications, being very efficient in keeping the system operating when there is functional loss of part of the system. Having at the end a low cost of hardware and zero cost in terms of software licenses.